Aqua-soluble DDQ reduces the levels of Drp1 and Aβ and inhibits abnormal interactions between Aβ and Drp1 and protects Alzheimer's disease neurons from Aβ- and Drp1-induced mitochondrial and synaptic toxicities. (13th June 2017) - Kuruva, Chandra Sekhar; Manczak, Maria; Yin, Xiangling; Ogunmokun, Gilbert; Reddy, Arubala P.; Reddy, P. Hemachandra
Abstract: The purpose of our study was to develop a therapeutic target that can reduce Aβ and Drp1 levels, and also can inhibit abnormal interactions between Aβ and Drp1 in AD neurons. To achieve this objective, we designed various compounds and their 3-dimensional molecular structures were introduced into Aβ and Drp1 complex and identified their inhibitory properties against Aβ-Drp1 interaction. Among all, DDQ was selected for further investigation because of 1) its best docking score and 2) its binding capability at interacting sites of Drp1 and Aβ complex. We synthesized DDQ using retro-synthesis and analyzed its structure spectrally. Using biochemical, molecular biology, immunostaining and transmission electron microscopy (TEM) methods, we studied DDQ's beneficial effects in AD neurons. We measured the levels of Aβ and Drp1, Aβ and Drp1 interaction, mRNA and protein levels of mitochondrial dynamics, biogenesis and synaptic genes, mitochondrial function and cell viability and mitochondrial number in DDQ-treated and untreated AD neurons. Our qRT-PCR and immunoblotting analysis revealed that reduced levels of mitochondrial fission and increased fusion, biogenesis and synaptic genes in DDQ-treated AD neurons. Our immunoblotting and immunostaining analyses revealed that Aβ and Drp1 levels were reduced in DDQ-treated AD neurons. Interaction between Aβ and Drp1 is reduced in DDQ-treated AD neurons. Aβ42 levels were significantly reduced in DDQ-treated mutant APPSwe/Ind cells. Mitochondrial number is significantly reduced and mitochondrial length is significantly increased. Mitochondrial function and cell viability were maintained in AD neurons treated with DDQ. These observations indicate that DDQ reduces excessive mitochondrial fragmentation, enhances fusion, biogenesis and synaptic activity and reduces Aβ42 levels and protects AD neurons against Aβ-induced mitochondrial and synaptic toxicities.